Tumor suppressor function of miR-127-3p and miR-376a-3p in osteosarcoma cells - Fellenberg, Jörg; Lehner, Burkhard; Schenker, Astrid; Kunz, Pierre (Cancers, 2019)
Since the introduction of high-dose chemotherapy about 35 years ago, survival rates of osteosarcoma patients have not been significantly improved. New therapeutic strategies replacing or complementing conventional chemotherapy are therefore urgently required. MicroRNAs represent promising targets for such new therapies, as they are involved in the pathology of multiple types of cancer, and aberrant expression of several miRNAs has already been shown in osteosarcoma. In this study, we identified silencing of miR-127-3p and miR-376a-3p in osteosarcoma cell lines and tissues and investigated their role as potential tumor suppressors in vitro and in vivo. Transfection of osteosarcoma cells (n = 6) with miR-127-3p and miR-376a-3p mimics significantly inhibited proliferation and reduced the colony formation capacity of these cells. In contrast, we could not detect any influence of miRNA restoration on cell cycle and apoptosis induction. The effects of candidate miRNA restoration on tumor engraftment and growth in vivo were analyzed using a chicken chorioallantoic membrane (CAM) assay. Cells transfected with mir-127-3p and miR-376a-3p showed reduced tumor take rates and tumor volumes and a significant decrease of the cumulative tumor volumes to 41% and 54% compared to wildtype cells. The observed tumor suppressor function of both analyzed miRNAs indicates these miRNAs as potentially valuable targets for the development of new therapeutic strategies for the treatment of osteosarcoma.
Gesehen am 14.02.2020